Is your mama a llaman - Guarino, Deborah; Kellogg, Steven (New York Scholastic, 1989)
A young llama asks his friends if their mamas are llamas and finds out, in rhyme, that their mothers are other types of animals.
Keywords: Fiction; Stories in rhyme